Combined experimental and computational insights into the key features of l-alanine l-alaninium picrate monohydrate: growth, structural, electronic and nonlinear optical properties1. Issue 67 (24th July 2015) - Muhammad, Shabbir; Shkir, Mohd.; AlFaify, S.; Irfan, Ahmad; Al-Sehemi, Abdullah G.
<x xml:space="preserve">Abstract</x> Comprising experimental and theoretical techniques we have highlighted the key features of LALAPM for electro-optical applications